Structural analysis of the TPI-Manchester, a thermolabile variant of human triosephosphate isomerase - Romero, Jorge Miguel (2024)
This is a preprint article, it offers immediate access but has not been peer reviewed. All content on this site: Copyright © 2023 Elsevier Inc., its licensors, and contributors. All rights are reserved, including those for text and data mining, AI training, and similar technologies. For all open access content, the Creative Commons licensing terms apply.